Rice varieties with resistance to multiple races of Magnaporthe oryzae offer opportunities to manage rice blast in Australia. (4th December 2016) - Fang, X.; Snell, P.; Barbetti, M.J.; Lanoiselet, V.
Abstract: Rice blast caused by Magnaporthe oryzae is the most destructive disease of rice worldwide. Development of resistant varieties is considered as the most cost‐effective and sustainable way to manage rice blast. However, there remains a lack of knowledge about the resistance of rice varieties to blast disease in Australia. This study was conducted to determine if there was any resistance existing among the rice varieties grown in Australia to M. oryzae isolates from this country that belong to different races. There was a resistant reaction of the variety SHZ‐2 to all the five races of IA‐1, IA‐3, IA‐63, IB‐3 and IB‐59, with a percent disease index (%DI) less than 40. Varieties NTR587, BR‐IRGA‐409, Ceysvoni and Rikuto Norin 20 showed a resistant reaction to races IA‐3, IA‐63, IB‐3 and IB‐59; and the variety Kyeema exhibited a resistant reaction to races IA‐3, IB‐3 and IB‐59. For the races IA‐1 and IB‐59 with more than one isolate, varieties with differential disease reactions across different isolates belonging to the same race were also revealed: five varieties, Langi, Opus, Sherpa, Viet 1 and Topaz, exhibited differential disease reactions to the three IA‐1 isolates; 10 varieties showed differential disease reactions to the four IB‐59 isolates; in addition, the varieties that had differential disease reactions to the IA‐1 isolates also exhibited differential disease reactions to the IB‐59 isolates of race. This study provides valuable resistance sources for breeding programmes to develop rice varieties with resistance to multiple races of M. oryzae in Australia.